2020
DOI: 10.1080/13683500.2020.1806791
|View full text |Cite
|
Sign up to set email alerts
|

The influence of foreigners’ buzzing on TripAdvisor ranking of restaurants in Venice: implications for the sustainability of over-touristed heritage cities

Abstract: Local and global coexist in any tourist destination, and the challenge of tourism sustainability is what remains in the balance between these two dimensions. Social and consumer-generated media are changing how local and global are coming together in the local system. These media's effects are even more important in overtouristed places, where a significant imbalance between local and tourist development already exists. In this paper, the effects from foreigners' reviews in crowd-based ranking systems in overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…So, like in Venice, an overtourism problem seems to make the destination less attractive due to the excessive number of visitors. This overtourism has led to a touristification of the city (Ganzaroli et al , 2021), as some comments of the visitors have revealed (e.g. many allusions to souvenirs and postcards or daily guided excursions).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, like in Venice, an overtourism problem seems to make the destination less attractive due to the excessive number of visitors. This overtourism has led to a touristification of the city (Ganzaroli et al , 2021), as some comments of the visitors have revealed (e.g. many allusions to souvenirs and postcards or daily guided excursions).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of technologies to improve connectivity, information systems and sensorization to solve overcrowding and to “better understand the movements of the tourists while at the destination, the relations they have with other tourists and residents and the places they visit” (Bulchand-Gidumal, 2022). The improvement of smart technologies will also contribute to solving the overtourism problem (Ganzaroli et al , 2021), and increase visitors’ satisfaction and positive eWOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Journal of Sustainable Tourism (H-index: 103) promotes the understanding of sustainability and its relationship with the tourism industry by stimulating The third scientific production period (2015-2021) counts 213 contributions. The themes of innovation and sustainability, resilience, e.g., [51,[103][104][105][106][107][108][109][110] and its related topics, such as disaster and crisis recovery, i.e., [104][105][106][107][108]; climate change, i.e., [111][112][113][114]; and overtourism, i.e., [115][116][117], start to emerge. Other papers stress the attention on smart destinations.…”
Section: Distribution Of Scientific Production In Journals Most Cited Articles and Main Authorsmentioning
confidence: 99%
“…prominent user-generated content platform for restaurants evaluation (Ganzaroli et al, 2020); (ii) it is considered the premier data source for empirical evidence (Xiang et al, 2017); and (iii) it is intensively used in academic research (Ganzaroli et al, 2020;Oktadiana et al, 2020;Pezenka & Weismayer, 2020;Ruiz-Mafe et al, 2020). Besides, as Ganzaroli et al (2017) point out, it provides an average quality score that comprises the main factors that affect restaurants' success on the market, namely: food, service, value for the money, and atmosphere.…”
Section: Hotel Intellectualmentioning
confidence: 99%